Relationship between uric acid, blood pressure and anthropometric indices in a healthy Ghanaian adult population - Quartey, Perez; Owusu, Bright Afriyie; Marfo, Lawrence; Appiah, Emmanuel (International Journal of Research in Medical Sciences, 2020)
Background: Age- and sex-dependent variations in the relationship between uric acid and blood pressure and anthropometric indices have been reported in some populations. However, this has not been studied in a Ghanaian adult population. Methods: Body mass index, waist circumference, blood pressure and serum uric acid levels were measured. Categorical differences were analysed with chi-square. Differences between groups were assessed by t-test and one-way analysis of variance. Association between serum uric acid and baseline characteristics of age, body mass index, waist circumference and blood pressure was assessed by Pearson’s correlation. Statistical significance was pegged at p<0.05. Results: Prevalence of hyperuricemia was 3.2%. There was no significant difference in prevalence of hypertension between males (28.6%) and females (28.9%). General obesity and central obesity prevalence were significantly higher among females. In males, serum uric acids levels had statistically non-significant positive correlations with age, blood pressure, waist circumference and body mass index. In females, the results showed that among women less than 45 years, serum uric acid had significant positive correlations with only body mass index and waist circumference. However, significant positive correlations were observed between all the baseline parameters and uric acid among women who are 45 years and above. Conclusions: Increasing serum uric acid levels are significantly associated with higher blood pressure, body mass index and waist circumference. This relationship is stronger in females than in males, with the age group ≥45 years being the main determinant of this relationship.